2012
DOI: 10.1016/j.actbio.2011.11.031
|View full text |Cite|
|
Sign up to set email alerts
|

Macrophage phenotype as a predictor of constructive remodeling following the implantation of biologically derived surgical mesh materials

Abstract: Macrophages have been classified as having plastic phenotypes which exist within a spectrum between M1 (classically activated; pro-inflammatory) and M2 (alternatively activated; regulatory, homeostatic). To date, the effects of polarization towards a predominantly M1 or M2 phenotype have been studied largely in the context of response to pathogen or cancer. Recently, M1 and M2 macrophages have been shown to play distinct roles in tissue remodeling following injury. In the present study, the M1/M2 paradigm was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

36
603
4
4

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 642 publications
(647 citation statements)
references
References 57 publications
36
603
4
4
Order By: Relevance
“…From this standpoint, PDO and PHVBB outperformed PU with regard to the predominance of infiltrating regulatory ED2 macrophages, a phenotype associated with less inflammatory tissue scarring and improved remodelling. 35,36 The enhanced ED2 response to PDO and PHBVV is consistent with our concurrent findings of higher expressions of the anti-inflammatory IL-10 cytokine and MCP-1 chemokine. In contrast, PU was associated with a much greater inflammatory response, with a persisting insulation of the patches and, occasionally, granulomas, which have also been reported in other applications.…”
Section: Figsupporting
confidence: 89%
“…From this standpoint, PDO and PHVBB outperformed PU with regard to the predominance of infiltrating regulatory ED2 macrophages, a phenotype associated with less inflammatory tissue scarring and improved remodelling. 35,36 The enhanced ED2 response to PDO and PHBVV is consistent with our concurrent findings of higher expressions of the anti-inflammatory IL-10 cytokine and MCP-1 chemokine. In contrast, PU was associated with a much greater inflammatory response, with a persisting insulation of the patches and, occasionally, granulomas, which have also been reported in other applications.…”
Section: Figsupporting
confidence: 89%
“…Brown et al revealed that increased numbers of M2 macrophages and higher ratios of M2:M1 macrophages could lead to more positive remodeling outcomes. [34] Given the potential of immune modulating scaffolds for wound healing, we then nail down those hydrogels that can support M2 macrophages. Unlike typical methods of validating scaffolds in vivo followed by characterizing the macrophage phenotype via histology, [41] we proactively examined the impact of macromers on macrophage phenotype in vitro, thus determining the pro-regenerative scaffolds.…”
Section: Discussionmentioning
confidence: 99%
“…Transition to an M2 phenotype occurs concurrently with resolution of the inflammatory process and the initiation of the remodeling phase of wound healing. [34] Once monocytes are differentiated into macrophages, polymers are added to examine how they affect the macrophage proliferation (n = 6) ( Figure 2Bi). Matristem powder (collagen extraction from pig bladder) showed significantly lower impacts on both day 2 and day 4, indicating it may not induce macrophage-related inflammation.…”
Section: Macrophage Differentiation and Polarizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, ECM materials derived via decellularization of a variety of allogeneic or xenogeneic source tissues have been shown to induce a phenotypic transition from the proinflammatory macrophage and lymphocyte phenotype toward a regulatory, "anti-inflammatory" and healing phenotype [9,31,32,33], and to promote endogenous stem/progenitor cell activation and recruitment [11,29,34,35].…”
Section: Discussionmentioning
confidence: 99%